Factors Influencing Consumer Satisfaction in Online Shopping: A Case of College Level Students (The International Research Journal of Management Science, 2023)
Purpose - The purpose of this study is to examine the influence and relationship between product quality, information availability, and shipping cost with customer satisfaction among college-level students in Kathmandu Valley.Design/methodology/approach – This research adopted the explanatory research design. The study targeted college-level students in Kathmandu Valley as a population. A total of 400 respondents were selected from the different colleges by using a convenience sampling technique. The questionnaire survey was applied to collect primary data. The study adopted cross tab, independent t-test, and correlation to analyze the data.Findings - The study shows that customer satisfaction is influenced and associated with product quality, information availability, and shipping costs in online shopping. The availability of information is a major factor in customer satisfaction with online shopping. Online shopping companies must uphold reliable websites, ensuring accurate and up-to-date information about products and services to attract potential customers. Additionally, they need to maintain the standard of quality for retaining existing customers and meeting their expectations in enhancing the company's reputation.Research limitation/implications - The study examines only three explanatory variables i.e., product quality, availability of information, and shipping cost so that future researchers can study other factors impacting customer satisfaction among college-level students of Kathmandu Valley in different geographic concentrations with new analytical tools.Originality/value –The study targeted college-level students of Kathmandu Valley as population. The study is based on the Technology Acceptance Model (TAM), developed by Fred Davis in 1986 to measure the results.